OPTIMALISASI PERAN PEMBIAYAAN MODAL KERJA DALAM PENINGKATAN PEREKONOMIAN MASYARAKAT DESA PRENDUAN : STUDI KASUS BPRS BHAKTI SUMEKAR CABANG PRAGAAN - Naili, Amaliyatun; Hidayat, Moh. Helmi; Elina, Riskiana (Accounting Department, Politeknik Negeri Bandung, 2025)
This study aims to determine how to optimize the role of working capital financing at Bank BPRS Bhakti Sumekar Pragaan Branch in improving the economy of the Prenduan village community and what are the challenges faced by Bank BPRS Bhakti Sumekar Pragaan Branch in optimizing working capital financing for the Prenduan village community. The research method used is descriptive qualitative research. The data sources collected were obtained through observation, interviews and documentation. With data analysis techniques using technical triangulation. The results of the study indicate that optimizing the role of working capital financing at BPRS Pragaan Branch in terms of welfare, access, participation, and control are the main indicators in empowering the community's economy. This is reflected in the implementation of aspects of planning, organizing, movement, and control optimally. However, there are several obstacles, such as late payments by customers, competition with other banks that offer lower interest rates, customer data recorded in the red at the OJK even though they have never had bad debts, and prospective customers who do not yet have a growing business.. Keywords: Optimization, Financing, Working Capital